Memories and representations of the “fear of madness” among doctors and psychiatric doctors (Research, Society and Development, 2020)
This article’s scope is to present results of the research about social and collective memories constructed by psychiatrists regarding the concept of mad and madness, based on the contributions made by the Theory of Memory and the Theory of Social Representation. We applied semi structured interviews to 10 physicians that are currently working (or have worked) with psychiatric patients for at least two years, having developed most of their professional activities in Vitória da Conquista - Bahia. In this work, we situate the course of social representations - both collective and individual - that have been shaped by these psychiatrists. As a result, we observed that the interviewees mobilized a representation of fear concerning the mad and madness, alongside a collective-individual memory of their experiences, as they pinpointed their personal and professional points of view, as well as their pairs and psychiatric references to construct a narrative of themselves and their profession, concerning the comprehension of the meaning of fear of the mad and of the madness.